The Utility of Point-of-Care Ultrasound in Emergency Medicine: A Hospital-Based Study in a Tertiary Care Centre in Telangana - Divya Raju Alluri; K. Venkat Ram Reddy; RK Reddy (Asian Journal of Medical Radiological Research, 2019)
Background: Point-of-care ultrasound (POCUS) is a valuable diagnostic tool in emergency medicine, providing real-time bedside imaging for rapid clinical decision-making. Unlike conventional radiology-based ultrasound, POCUS allows immediate assessment of critically ill patients. Its applications range from trauma assessment using the FAST protocol to procedural guidance and diagnosis of conditions such as pneumothorax, cardiac tamponade, and abdominal aortic aneurysm. Despite its growing integration into emergency medicine, there is limited regional data on its effectiveness in Indian tertiary care settings. This study evaluates the role of POCUS in emergency medicine at SVS Medical College & Hospital, Mahabubnagar, Telangana, assessing its impact on diagnostic accuracy, patient management, and clinical outcomes. Objectives: The primary objective was to evaluate the diagnostic efficacy and clinical utility of POCUS in the emergency department (ED). The study aimed to assess its impact on early diagnosis, procedural guidance, and patient management. Secondary objectives included analyzing the frequency of POCUS utilization across different emergency conditions, its accuracy compared to conventional imaging, and its role in reducing time to intervention and hospital stay duration. Subjects and Methods: This prospective hospital-based observational study was conducted at SVS Medical College & Hospital, Mahabubnagar, Telangana, over six months, starting from January 2018. A total of 100 patients requiring ultrasound-based assessment in the ED were included. POCUS was performed by trained emergency physicians. Data were collected on patient demographics, clinical presentation, indication for ultrasound, findings, subsequent management, and final diagnosis. The diagnostic accuracy of POCUS was compared to confirmatory imaging modalities, including formal radiology-based ultrasound, CT, or MRI. Time to definitive diagnosis and treatment initiation was recorded. Statistical analysis was conducted to determine the sensitivity, specificity, and predictive value of POCUS in various emergency scenarios. Results: POCUS significantly enhanced diagnostic accuracy and expedited clinical decision-making. It was most frequently used in trauma (FAST examination), suspected pneumothorax, cardiac emergencies (pericardial effusion, tamponade), abdominal pain (hepatic, renal, biliary pathology), and vascular access guidance. The overall sensitivity and specificity of POCUS for major emergency conditions were 89.4% and 92.1%, respectively, compared to gold-standard imaging. POCUS facilitated early detection of life-threatening conditions, reducing median time to definitive intervention by 45 minutes compared to conventional imaging pathways. In trauma cases, FAST ultrasound accurately identified intra-abdominal bleeding in 85% of cases, correlating well with CT findings. Additionally, POCUS was highly effective for procedural guidance, reducing complications in central venous catheterization by 30%. Conclusion: POCUS is an indispensable tool in emergency medicine, enabling rapid and accurate bedside diagnostics that improve patient outcomes. This study highlights its crucial role in early detection of critical conditions, expediting clinical decision-making, and reducing time to intervention. Integrating POCUS into routine ED protocols can significantly enhance patient care. Future studies should focus on expanding training programs for emergency physicians to optimize POCUS benefits.